Rhabdomyolysis Complicated by Compartment Syndrome Treated with Traditional Korean Medicine Treatments: A Case Report - Youngkyung Kim; Hwayeon Ryu; Hyun Lee; Jaehui Kang (Journal of Acupuncture Research)
This study aimed to report the effect of traditional Korean medicine (TKM) on a patient with rhabdomyolysis complicated by compartment syndrome who presented with leg pain and hypoesthesia. TKM including acupuncture, pharmacopuncture (bee venom), herbal medicine, moxibustion, and physiotherapy was used to treat the patient. The patient was assessed according to the symptoms, numerical rating scale (NRS) for pain daily and digital infrared thermal imaging for the assessment of body temperature weekly. As treatment progressed, the NRS decreased from 10 to 3–8 depending on the patient’s leg area and from 10 to 1 for the subjective degree of hypoesthesia. In addition, as the patient showed signs of improvement, the degree of temperature drop in the lower extremities improved. These results show the effectiveness of TKM for the treatment of leg pain and hypoesthesia caused by rhabdomyolysis.